Proyecto de factibilidad para la creación de una empresa de comercialización y distribución de productos de primera necesidad en la Parroquia de Tambillo - Rojas Collaguazo, Diego Alejandro (2010)
Research on the marketing and distribution of consumer products in the area of Tambillo and around main purpose is to improve the quality of life of the inhabitants accessing staples without intermediaries, so that they can pay fair prices. The company is geared to function as a regulator of prices as it tries to avoid speculation of intermediaries, arriving with wholesale prices directly to the customer.